Measuring optimism bias among military personnel. (October 2021) - Cutello, Clara Alida; Walsh, Clare; Foerster, François Remy; Hanoch, Yaniv; Hellier, Elizabeth
Highlights: This is one of the few studies to experimentally study optimism bias in military personnel. The study results will be of interest to a wide spectrum of academics and non-academic audiences (police, policymakers, fire and rescue services, military bases). With car accidents representing the main cause of death for individuals and young military personnel aged 16–25 years, the present results have clear implications for the design and implementation of preventive programs across the globe. The results will be of interest to the general public as well as a range of media outlets. Abstract: High numbers of young military personnel die due to road traffic collisions (RTCs). Yet, there is a paucity of research related to the contributing factors (i.e., optimism bias and willingness to take risks) associated with RTCs and the examination of road safety education program tailored at reducing young military fatalities. In order to address this gap in the literature, we examined one specific road safety educational intervention tailored for the UK military personnel and investigated their attitudes towards the program, optimism bias and willingness to take risks. Measures evaluating their optimism bias, willingness to take risks and attitudes towards the program were asked after the participants attended the road safety interventions. The results revealed that young military personnel, aged 18–25, had higher optimism bias and willingness to take risks compared to older military personnel, and that this effect diminishes with age. The results provide importance evidence related to military personnel's attitudes to risk-taking.